The application of Trindex to predict harmful algal blooms in lake torment (Nova scotia, Canada) - Hushchyna, Kateryna; Bao, Quoc Vo; Tri, Nguyen-Quang (Видавництво Львівської політехніки, 2020)
This paper introduces the Threshold Index (hereafter called TRINDEX) for the Harmful Algal Bloom (HAB) prediction in lake Torment (Nova Scotia province, Canada). TRINDEX was suggested via the logarithmic transformation and then the thresholds of bloom pattern were established by the discrimination test named the Receiver Operating Characteristic curve (ROC). The cohort studies will be also presented to show how accurate the bloom prediction when using TRINDEX in comparing to the real observations.
Keywords: Harmful Algal Bloom (HAB); Threshold Index (TRINDEX); Cohort studies; Receiver Operating Characteristic (ROC) curve